Is Single-stage Microvascular Reconstruction for Facial Mucormycosis Safe? - R. Parvati; M. V. Subbalaxmi; R. Srikanth; P. Sajani; R. V. Koteswara Rao (Indian Journal of Plastic Surgery)
Introduction This is a retrospective therapeutic series of eight cases of facial mucormycosis treated over a 15-year period to determine the safety of simultaneous debridement and free-flap reconstruction in facial mucormycosis. Methods Surgical debridement was done for three cases that presented acutely with systemic manifestations (group 1) and five cases that presented in the subacute phase without systemic manifestations (group 2). The debridement involved total maxillectomy with orbital exenteration in three cases, total maxillectomy with orbital preservation in two, and subtotal maxillectomy in three cases. A total of seven out of eight patients underwent reconstruction with free flap for defect closure; in one patient, only primary closure of mucosa was done. Results The mean follow-up was 20.5 months. Two patients with acute disease, where reconstruction was done, died in the postop period (on the 27th and 6th day post reconstruction, respectively) due to continuing infection and septic shock. One of the three (group 1), who presented acutely and underwent debridement alone, survived. Four of five patients in group 2 underwent successful free-flap reconstruction. The patient with free-flap loss was salvaged with an extracorporeal radial forearm flap. All except one patient had a soft-tissue free-flap reconstruction. Three of the six living patients reported for secondary surgery. The inability to achieve clear nonnecrotic surgical margins due to extensive disease was the reason for mortality in two patients in group 1. There was no mortality in any of the group 2 patients, even when debridement and free-flap coverage was done simultaneously. Conclusion Simultaneous debridement and free flap can be successfully implemented in select cases of facial mucormycosis